2013
DOI: 10.3389/fonc.2013.00214
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Recovery and Subsequent Chemotherapy Following Radiolabeled Anti-Prostate-Specific Membrane Antigen Monoclonal Antibody J591 in Men with Metastatic Castration-Resistant Prostate Cancer

Abstract: Radioimmunotherapy (RIT) has demonstrated efficacy with acceptable toxicity leading to approval in non-Hodgkin’s lymphoma, but has been slower to develop for the treatment of advanced solid tumors. Prostate cancer (PC) represents a good candidate for RIT based upon high exposure to circulating antibodies at common disease sites with a specific, highly expressed cell-surface antigen of prostate-specific membrane antigen. Four phase I and II trials utilizing 177Lu- or 90Y-J591 have been reported. Long-term toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 31 publications
2
35
1
2
Order By: Relevance
“…The long circulation times of monoclonal antibody–based radioimmunotherapy is a disadvantage when it comes to myelosuppression, but is advantageous for continuous delivery and uptake of radionuclides by tumor over many days. In contrast to the high incidence of low‐grade xerostomia in prospective studies of 177 Lu‐targeted radioligand therapy, we have not observed this phenomenon (nor targeting of salivary glands by imaging) . Renal toxicity is a potential late side effect of PSMA radioligand therapy .…”
Section: Discussioncontrasting
confidence: 71%
See 4 more Smart Citations
“…The long circulation times of monoclonal antibody–based radioimmunotherapy is a disadvantage when it comes to myelosuppression, but is advantageous for continuous delivery and uptake of radionuclides by tumor over many days. In contrast to the high incidence of low‐grade xerostomia in prospective studies of 177 Lu‐targeted radioligand therapy, we have not observed this phenomenon (nor targeting of salivary glands by imaging) . Renal toxicity is a potential late side effect of PSMA radioligand therapy .…”
Section: Discussioncontrasting
confidence: 71%
“…Renal toxicity is a potential late side effect of PSMA radioligand therapy . No long‐term follow‐up has been performed with PSMA‐targeted radioligand therapy, but we have not observed any significant acute or delayed nephrotoxicity in our studies with many years of follow‐up …”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations